Politik Modern Turki: Sekularisme, Islamisme, dan Perbandingan Atatürk dan Erdoğan: Modern Turkish Politics: Secularism, Islamism, and a Comparison of Atatürk and Erdoğan - Abdullah Mufid Mubarrok; Rubaidi; Mohammad Sholeh (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2025)
This article examines the historical and political dynamics between secularism and Islamism in the context of modern Turkey, with a focus on two central figures: Mustafa Kemal Atatürk and Recep Tayyip Erdoğan. Atatürk, as the founder of the Republic of Turkey, established the foundations of the state based on principles of secularism and Western modernism, including the abolition of the Caliphate and reforms in law, education, and public symbols. In contrast, Erdoğan and the Justice and Development Party (AKP) have integrated Islam into national identity through policy reforms, education, and historical discourse. Drawing on perspectives from the politics of religion and political sociology, and employing conceptual frameworks such as Public Religion and Political Islam, this article adopts a qualitative research approach based on library research and Norman Fairclough’s critical discourse analysis to trace the relationship between discourse, power, and the construction of national identity, as well as the ideological dynamics between secular and religious groups in Turkey’s contemporary public sphere. The findings indicate that despite their differing approaches to religion, both Atatürk and Erdoğan employed centralized and symbolic forms of power to shape national narratives. This study contributes to a deeper understanding of state–religion relations in the politics of the modern Muslim world, offering a critical reflection on the future of democracy, pluralism, and religious freedom in Turkey.